2017
DOI: 10.1080/02640414.2017.1287935
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the virtual elevation method to evaluate rolling resistance of different mountain bike cross-country tyres

Abstract: Although a low rolling resistance is advantageous in mountain bike cross-country racing, no studies have used the virtual elevation method to compare tyres from different manufacturers as used in international competitions so far. The aims of this study were to assess the reliability of this method, to compare the off-road rolling resistance between tyres and to calculate the influence on off-road speed. Nine 29-in. mountain bike cross-country tyres were tested on a course representing typical ground surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Chung (2012) originally proposed the virtual elevation method to determine C r and C d A. Maier et al (2018) later evaluated the method for off-road use and showed it to be reliable (with a typical error of 2.8%) for estimating C r in off-road conditions. Briefly, elevation profiles are calculated from recorded speed and power output data.…”
Section: Virtual Elevation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chung (2012) originally proposed the virtual elevation method to determine C r and C d A. Maier et al (2018) later evaluated the method for off-road use and showed it to be reliable (with a typical error of 2.8%) for estimating C r in off-road conditions. Briefly, elevation profiles are calculated from recorded speed and power output data.…”
Section: Virtual Elevation Methodsmentioning
confidence: 99%
“…The correct values can be determined by making iterative adjustments to the unknown C r and C d A while optically verifying the resulting elevation profile. As Maier et al (2018) have suggested, we estimated both the C r and the C d A when analysing the C d A tests and used a fixed C d A for each rider for the subsequent C r estimations. Three investigators blinded to the wheel set analysed all tests using a cycling performance software (Golden Cheetah 3.1, www.goldenchee tah.org); their estimates were then averaged for further analysis.…”
Section: Virtual Elevation Methodsmentioning
confidence: 99%
See 3 more Smart Citations